The end of the car as we knew it? Automobile subjectivities in change. (PROKLA. Journal of Critical Social Science, 2018)
Changing automobile subjectivities - are we on the brink of the end of the car as we knew it? Automobility is in a state of flux. How is its cultural meaning changing against the background of increasing digitalization and the foreseeable electrification of car traffic? On the one hand, intermodal mobility practices indicate a certain loss of significance of the car, while, on the other hand, the SUV-boom is an expression of a growing social polarization and revaluation of the car. The article concludes that there are currently only view signs of erosion but clear signals for a renewal of automobility under the conditions of flexible capitalism.
Keywords: auto mobility; History of the car; SUVs; digital capitalism; Mobility